Emotional Intelligence and Autonomous Learning in Student Cyberbullying in Times of Covid-19 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research entitled: "Emotional intelligence and autonomous learning in cyberbullying of students of the Educational Institution" Francisco Bolognesi ", 2020", aimed to determine the incidence of emotional intelligence and autonomous learning in cyberbullying, and responds to the problem institutional educational. The study is explanatory, obeys a quantitative approach and a non-experimental, causal correlational, cross-sectional design; with a sample comprised of 99 students, to whom questionnaires were applied to collect data on each of the variables. After the analysis and interpretation of the results, the following conclusion was reached: Emotional intelligence and autonomous learning had a significant impact on cyberbullying of the students of the “Francisco Bolognesi” Educational Institution in Villa el Salvador; having obtained a result in the linear logistic regression test p-value = 0.000.